To solve the equation 5/3x + 11/3 = -4/3, we can follow these steps:
Step 1: Subtract 11/3 from both sides of the equation:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
5/3x = -15/3
Step 2: Simplify the right side of the equation:
5/3x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
1x = -3
Therefore, the solution to the equation is: 5/3x = -5, x = -3.
the equation 5/3x +11/3= -4/3 solved as follows. supply the correct numbers to complete the solution 5/3x = __ subtract 11/3 to both sides x= __ multiply both dides bye 3/5 the reciprical of 5/3
1 answer